Acetohydroxyacid synthase (AHAS)-inhibitor herbicide resistance detected in recent Alopecurus myosuroides (black-grass) incursions into New Zealand - Buddenhagen, Christopher E.; Gunnarsson, Matilda; Hackell, Deborah L.; Lawrie, Ivan; Ngow, Zachary; Mills, Ashley; Ryder, Tim (New Zealand Plant Protection, 2026)
Alopecurus myosuroides Huds. (black-grass) has become problematic globally due to its repeated evolution of herbicide resistance. Three incursions via contaminated seed lots have occurred in the past 20 years despite strict border biosecurity in New Zealand. However, it is not known if the black-grass populations linked to these incursions carried herbicide resistance. Enough seed was obtained from contaminated seed lots (ryegrass-linked population UK2007; linseed-linked population FR2021) for a dose–response assay to test resistance to a commercial herbicide product containing both iodosulfuron and mesosulfuron, used for black-grass control in Europe, but not enough for repetition of the experiment or to test multiple herbicides. Seed lot FR2021 showed a high level of resistance, requiring 250g ai/ha to achieve 90% control (LD90) more than ten times the label rate whereas seed lot UK2007 had an LD90 of 19.0 g ai/ha almost twice the label rate (10 g ai/ha). Acetohydroxyacid synthase (AHAS)-inhibitor herbicides should not be used against black-grass populations during incursion responses in New Zealand. Any future black-grass incursions will be increasingly likely to carry herbicide resistance traits. Strong border measures, certified seed use, avoiding seed sourced from infested areas and screening for resistance are critical for prevention and effective control of black-grass incursions.